Clinicopathologic characteristics, treatment outcomes, and prognostic factors of primary thoracic soft tissue sarcoma: A multicenter study of the Anatolian Society of Medical Oncology (ASMO) - Unal, Olcun Umit; Oztop, Ilhan; Yasar, Nurgul; Urakci, Zuhat; Ozatli, Tahsin; Bozkurt, Oktay; Yilmaz, Ahmet Ugur (Wiley, 2015)
BackgroundSoft tissue sarcomas (STSs) are rare malignant tumors of embryogenic mesoderm origin. Primary thoracic STSs account for a small percentage of all STSs and limited published information is available. This study aimed to identify the prognostic factors for thoracic STSs and evaluate the disease's clinical outcomes. MethodsThe medical records of 109 patients with thoracic STSs who were treated between 2003 and 2013 were retrospectively reviewed. Patients' survival rates were analyzed and potential prognostic factors evaluated. ResultsThe median follow-up period was 29 months (range: 1-121 months). STSs were most frequently localized on the chest wall (n = 42; 38.5%) and lungs (n = 42; 38.5%). The most common histological types were malignant fibrous histiocytoma (n = 23; 21.1%), liposarcoma (n = 17; 15.6%), and leiomyosarcoma (n = 16; 14.7%). The median survival time of all patients was 40.3 months (95% confidence interval, 14.22-66.37 months), with one and five-year survival rates of 93.4% and 63.5%, respectively. Univariate analysis of all groups revealed that metastatic stage, unresectability, tumor diameter of >10cm, tumor location other than the chest wall, and grade 3 diseases were predictable of poor survival. However, only grade 3 diseases and tumor location other than the chest wall were confirmed by multivariate analysis as poor prognostic factors. ConclusionsPrimary thoracic STSs are rarely seen malignant tumors. Our results indicated that patients with low-grade tumors and those localized on the chest wall often experienced better survival outcomes.
Keywords: Primary thoracic soft tissue sarcoma; prognostic factors; treatment